Chinese EFL Teachers' Cognition about the Effectiveness of Genre Pedagogy: A Case Study. (August 2019) - Shi, Leimin; Baker, Amanda; Chen, Honglin
Developing students' communicative competence became the primary goal of the current College English Curriculum Requirements in 2004 in China. There has been increasing concern, however, that this goal has yet to be realized, particularly in relation to the teaching of writing. This study investigated the potential of a Systemic Functional Linguistics (SFL-) informed genre approach to enhance Chinese students' communicative competence in writing. As teachers' beliefs have a strong impact on the effectiveness of their teaching practice (Borg, 2003), the study examined six Chinese College English teachers' shifts in their beliefs and practices after attending a training workshop in the genre-based approach to writing development. Using pre- and post- workshop interviews and classroom observations and drawing on the analytical frameworks of teacher cognition (Borg, 2003), teacher knowledge (Shulman, 1986) and interactional scaffolding (Hammond and Gibbon, 2005), the study found that professional training in SFL genre pedagogy had a positive impact on teachers' cognition about writing instruction, albeit with one notable constraint; the teachers paid only partial attention to the social purpose of the targeted genre, thus limiting the successful implementation of the pedagogy to a certain extent.